2019
DOI: 10.3389/fpsyg.2019.00631
|View full text |Cite
|
Sign up to set email alerts
|

Selective Emotional Dysregulation in Splenium Agenesis. A Case Report of a Patient With Normal Cognitive Profile

Abstract: Objective: Patients with lesions of the corpus callosum are rare and may present different symptoms of the disconnection syndrome. However, to-date studies on callosotomized patients have not been conclusive, likely because of the non-uniform nature of clinical features, the extent of resection, and methods used to investigate specific and related deficits. Agenesis of the corpus callosum (AgCC) may be asymptomatic and discovered incidentally or associated with very slight deficits diagnosed during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…61 Also, there have been reports of emotional dysregulation in splenium agenesis. 62 Regarding the chronicity and recurrent episodes of our participants, chronic and recurrent deteriorations in the whitematter integrity of the corpus callosum might be reflected in WMC reductions in both the genu and splenium of the corpus callosum. Consistent with numerous previous brain imaging findings, the present study also found significantly lower GMC in various brain regions, including the mid-frontal, 5,63 temporal, 63 cingulate, [11][12][13]63 insular, 63 amygdala, [64][65][66][67][68] hippocampal, 19,69,70 hypothalamic, and thalamic 71 regions in patients with MDD compared to HCs.…”
Section: A B Cmentioning
confidence: 84%
See 1 more Smart Citation
“…61 Also, there have been reports of emotional dysregulation in splenium agenesis. 62 Regarding the chronicity and recurrent episodes of our participants, chronic and recurrent deteriorations in the whitematter integrity of the corpus callosum might be reflected in WMC reductions in both the genu and splenium of the corpus callosum. Consistent with numerous previous brain imaging findings, the present study also found significantly lower GMC in various brain regions, including the mid-frontal, 5,63 temporal, 63 cingulate, [11][12][13]63 insular, 63 amygdala, [64][65][66][67][68] hippocampal, 19,69,70 hypothalamic, and thalamic 71 regions in patients with MDD compared to HCs.…”
Section: A B Cmentioning
confidence: 84%
“…Recently, studies have been conducted on the role of the splenium in depression, and reductions in the axonal myelin of the splenium in MDD patients was reported [ 61 ]. Also, there have been reports of emotional dysregulation in splenium agenesis [ 62 ]. Regarding the chronicity and recurrent episodes of our participants, chronic and recurrent deteriorations in the whitematter integrity of the corpus callosum might be reflected in WMC reductions in both the genu and splenium of the corpus callosum.…”
Section: Discussionmentioning
confidence: 99%
“…In celebrating the achievements of Women in brain health and clinical neuroscience , we not only honor their individual contributions but also challenge the prevailing norms that hinder the full realization of their potential. Our continually evolving neurocognitive model, grounded in advancements concerning social cognition (Morese and Palermo, 2020 , 2022 ), metacognitive-executive functions and their intricate interactions with neurodegenerative diseases (Morese et al, 2018 ; Palermo et al, 2018 ), acquired brain injuries and pathologies (Palermo et al, 2014 , 2019 ), represents a step toward creating a future where talent is recognized and celebrated regardless of gender. This approach fosters an environment where the scientific community thrives on the diverse perspectives and experiences that women bring to the table, emphasizing the importance of inclusivity and equity in advancing research and innovation.…”
mentioning
confidence: 99%